EXPERIMENTAL STUDY OF EFFECTIVENESS OF DEEP FLUORIDATION OF ENAMEL DURING SECONDARY MINERALIZATION OF THE PERMANENT TEETH ENAMEL - H. V. Sorochenko (Український стоматологічний альманах, 2018)
Introduction. Increased risk of dental caries of permanent teeth in childhood corresponds to the period of secondary mineralization (5-15 years). The main pathogenetic direction of caries prevention in this period is to increase the level of mineralization of tooth enamel. High efficiency of caries prevention with fluoride preparations is associated with exposure to fluoride at different stages of dental caries pathogenesis, including the kinetics of the process of mineralization. Among the advantages of method of deep fluoridation of enamel (A.Knappvost, 1986) there are its painlessness, duration (3 minutes) and multiplicity of procedures (once every 6 months).